2018
DOI: 10.1016/j.ecoleng.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Potential of restoration of gravel-sand pits for Bats

Abstract: Restoration management of quarries is one of the major tasks in global restoration ecology due to the magnitude of impacts link with extraction activities and the potential conservation value of these post-industrial sites. However, identifying a target to reach can be challenging as ecological issues can be numerous and post-exploitation state can differ from the original due to ecosystems removal or topography alterations caused by exploitation. Here, we assess the restoration potential of gravel-sand pits f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
2
10
0
Order By: Relevance
“…Similar results have been reported for different types of taxa (e.g. Šálek ; Vojar et al ; Kerbiriou et al ). In this context, restored gravel pits could be functioning as substitute habitats analogous to natural lagoons by providing nursery, refuge and foraging for semiaquatic species in those anthropogenic landscapes where natural semiaquatic habitats have been lost.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results have been reported for different types of taxa (e.g. Šálek ; Vojar et al ; Kerbiriou et al ). In this context, restored gravel pits could be functioning as substitute habitats analogous to natural lagoons by providing nursery, refuge and foraging for semiaquatic species in those anthropogenic landscapes where natural semiaquatic habitats have been lost.…”
Section: Discussionsupporting
confidence: 91%
“…For example, Šebelíková et al () studied restored coal mines in Central Europe and found that plant species richness was higher on spontaneously revegetated sites than in sites restored following forestry reclamation methods. Moreover, the restoration of gravel pits and open mining sites have been usually reported to progressively increase local biodiversity, for example for birds (Šálek ), amphibians (Vojar et al ), and bats (Kerbiriou et al ). There are even occasions where natural spontaneous succession may facilitate gravel pit restoration (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been increasing interest in the potential of restored mineral sites to deliver ecosystem services (ES) and nature conservation (Tropek et al 2010;Larondelle & Haase 2012;Blaen et al 2016;Wilker et al 2016;Kerbiriou et al 2018). The restoration to agricultural land is still a common end-point of restoration plans, even though this may be a more expensive option (Davies 2006;Blaen et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…31 Restoration of the site after dismantling the turbines is necessary and will benefit all fauna species, including bats, especially on sites extensively modified during the construction of the farm. 92 , 93 …”
Section: Avoidance and Mitigationmentioning
confidence: 99%